After Lomé: the next 20 years - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
June 23 2000, a new Partnership Agreement was signed in Cotonou, Benin, between the ACP States and the European Community and its Member States